A non-Hermitian loop for a quantum measurement - Luis E F Foa Torres; Stephan Roche (Journal of Physics Communications)
Here we present a non-Hermitian framework for modeling state-vector collapse under unified dynamics described by Schrödinger’s equation. Under the premise of non-Hermitian Hamiltonian dynamics, we argue that collapse has to occur when the Hamiltonian completes a closed loop in the parameter space encoding the interaction with the meter. For two-level systems, we put forward the phenomenon of chiral state conversion as a mechanism for effectively eliminating superpositions. This perspective opens a way to simulate quantum measurements in classical systems that up to now were restricted to the Schrödinger part of the quantum dynamics.